Monitoring of the Invasive Round Goby (Neogobius melanostomus) in an Estuarine Seascape Based on eDNA - Leon Green; Marina Panova; Thomas G. Dahlgren; Alizz Axberg; Matthias Obst; Per Sundberg (Environmental DNA)
ABSTRACT In marine environments, nonindigenous species (NIS) are especially difficult to manage since they are often first detected when fully established and near impossible to eradicate. The development and implementation of effective monitoring methods for marine NIS are therefore crucial for early detection valuable to management. In this study, we develop and evaluate environmental DNA monitoring using quantitative digital PCR (dPCR) to assess the presence of the euryhaline round goby (Neogobius melanostomus) in a seascape environment close to Scandinavia's largest shipping port. We developed a dPCR assay for the species, targeting a region of the 12S gene, and verified its specificity compared to other locally common species from the gobiid family. Using captive live fish, we also experimentally determined the decaying rate of N. melanostomus DNA in water to a half‐life of 9.8 h in 15 ppt salinity and 15°C. Finally, we sampled 10 sites within a 400 km2 area using eDNA, fyke nets, and baited remote video to validate the accuracy of the water samples to predict the presence and abundance of the species. We found that the number of DNA copies extracted from the water samples varied strongly at sites where N. melanostomus were caught in nets or on video, but the average value from four water samples significantly correlated with an average value from four video samples and also with the total catch at each site. The eDNA assay also detected signals from the species at sites where no fish were caught by fishing or on video. These results show that this method is sensitive for the species at low abundance, and with enough replicates, it can be possible to determine the relative abundance between sites.